Hand gesture recognition through capacitive sensing : a thesis presented in partial fulfilment of the requirements for the degree of Master of Engineering in Electronics & Computer Engineering at Massey University, School of Food and Advanced Technology (SF&AT), Auckland, New Zealand - Xu, Muqing (Massey University, 2022)
This thesis investigated capacitive sensing-based hand gesture recognition by developing and validating through custom built hardware. We attempted to discover if massed arrays of capacitance sensors can produce a robust system capable of simple hand gesture detection and recognition. The first stage of this research was to build the hardware that performed capacitance sensing. This hardware needs to be sensitive enough to capture minor variations in capacitance values, while also reducing stray capacitance to their minimum. The hardware designed in this stage formed the basis of all the data captured and utilised for subsequent training and testing of machine learning based classifiers. The second stage of this system used mass arrays of capacitance sensor pads to capture frames of hand gestures in the form of low-resolution 2D images. The raw data was then processed to account for random variations and noise present naturally in the surrounding environment. Five different gestures were captured from several test participants and used to train, validate and test the classifiers. Different methods were explored in the recognition and classification stage: initially, simple probabilistic classifiers were used; afterwards, neural networks were used. Two types of neural networks are explored, namely Multilayer Perceptron (MLP) and Convolutional Neural Network (CNN), which are capable of achieving upwards of 92.34 % classification accuracy.
Figures 1.1, 1.2, 1.3, 2.1, 2.3 & 2.4 are re-used with permission. Figure 2.2 (=Smith, 1996 Fig 1) ©1996 by International Business Machines Corporation was removed.
Keywords: 400709 Medical robotics